TANAH ABSENTEE DARI WARISAN KELUARGA DI DESA DAYA MURNI JALUR 16 MUARA SUGIHAN BANYUASIN DALAM PERSPEKTIF HUKUM KELUARGA ISLAM - Eka Rustiana; Heri Junaidi; Antoni Antoni (Usroh: Jurnal Hukum Keluarga Islam, 2021)
Absentee Land from Family Heritage In Daya Murni Village Jalur 16 Muara Sugihan Banyuasin In The Perspective of Islamic Family Law, problem that occurred in the community about absentee inheritance land that isn’t directly utilized by the heirs but managed by the community. Based on this, this study will further examine it on How to empower and review Islamic Family Law on absentee land from heritage in Daya Murni Village Jalur 16 Muara Sugihan. The research method used is field research, the data source used is the primary data source obtained from interviews with respondents in the field, then secondary and primary data. Using qualitative descriptive methods, then analyzed to determine Islamic family law against the prohibition of absentee land ownership and it's utilization. research stated, Absentee land obtained from the heritage in the Village Daya Murni Line 16 Muara Sugihan isn’t in line with the Basic Agrarian Law of the Republic of Indonesia, economic side of the community isn’t left abandoned and managed village community. Islamic Family Law Review Against the Utilization of absentee land obtained from the inheritance hasn’t awakened the values of sakinah both within the family sphere and in the social sphere. Keywords: Absentee Land, Inheritance, Islamic Family Law